1981
DOI: 10.1007/bf02535681
|View full text |Cite
|
Sign up to set email alerts
|

Thiobarbituric acid reaction of methyl arachidonate monohydroperoxide isomers

Abstract: Methyl ester of monohydroperoxy eicosatetraenoic acid (MeHPETE) was prepared from methylene blue sensitized photooxidation products of methyl arachidonate. The thiobarbituric acid (TBA) value of MeHPETE was increased by adding ferrous sulfate to the reaction mixture. A linear relationship existed between the TBA value and the concentration of MeHPETE when ferrous sulfate was added. By using high performance liquid chromatography, MeHPETE was separated into 5 fractions whose isomeric compositions were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…TBARS have been often measured as an indirect index of lipid peroxides. The stoichiometry of the formation of TBARS from several positional isomers of HPETEs has been reported previously (Nakamura et al, 1978;Terao and Matsushita, 1981). It was found that 15-HPETE and 5-HPETE were most reactive substances for the TBA reaction in the presence of ferrous ion.…”
Section: Discussionsupporting
confidence: 71%
“…TBARS have been often measured as an indirect index of lipid peroxides. The stoichiometry of the formation of TBARS from several positional isomers of HPETEs has been reported previously (Nakamura et al, 1978;Terao and Matsushita, 1981). It was found that 15-HPETE and 5-HPETE were most reactive substances for the TBA reaction in the presence of ferrous ion.…”
Section: Discussionsupporting
confidence: 71%
“…The combined peroxidative changes of several chemical species in fresh tissues homogenates can be measured by means of the TBA assay procedures proposed by Masugi and Nakamura (27) Masugi and Nakamura (27) and Mihara et al (28), the preexisting malonaldehyde level was rather low, and intact PUFA remained substantially unchanged while "injured" PUFA changed to TBA-RS. On the other hand, Matsushita et al (29,30) studied the process of coloration in the TBA test of purified fatty acid monohydroperoxide. They demonstrated that metal salts, such as reduced iron, are useful for the release of TBA-RS from lipid hydroperoxide, and that oxygen is not needed for this reaction (31).…”
Section: Discussionmentioning
confidence: 99%
“…The assay was done by a modification of the method detailed by Terao and Matsushita (1981). Fractions were suspended in acetone to a final concentration of 0.1% v/v in 10 mL.…”
Section: Antioxidant Assaymentioning
confidence: 99%